90. Strength and respiratory evaluation in ALS: A follow up study. Issue 1 (January 2015) - Ceccanti, M.; Cambieri, C.; Capua, G.; Lopergolo, D.; Frasca, V.; Gabriele, M.; Inghilleri, M.
<x xml:space="preserve">Abstract</x> Amyotrophic lateral sclerosis is a degenerative disease involving upper and lower motor neurons, thus leading to progressive spasticity and weakness. Purpose of this study is to relate reduction in cMAP amplitude to functional impairment in ALS patients. We recruited 156 patients, 50 with bulbar, 106 with spinal onset. Patients were periodically visited every 3 month; medial plantar, ulnar and frenic nerves were examined in each patient. ALSFRS-R scale and MRC scale for strength were submitted; forced vital capacity and oxygen saturation were measured. In spinal onset patients, plantar medial reduction correlated to MRC for ipsilateral limb decrease between visit 1–2 (p = 0.034) and 1–3 (p = 0.006). Reduction in plantar medial cMAP in visit 1–3 and 1–4 correlated to FVC impairment in the same period (p = 0.037 and 0.008, respectively). Frenic cMAP decline between visit 1 and 4 was associated to ALSFRS impairment in respiratory items (p = 0.033). In bulbar onset, plantar medial reduction correlated to MRC for ipsilateral limb decrease between visit 1–2 (p = 0.002) and 1–3 (p = 0.044). Ulnar reduction between visit 1 and 4 was related to MRC for ipsilateral limb (p = 0.002), ALSFRS spinal (p = 0.032) and total (p = 0.028) score reduction. All these data are demonstrating a key-role of cMAP examination in monitoring strength and respiratory failure in ALS patients.